1987
DOI: 10.1126/science.3120313
|View full text |Cite
|
Sign up to set email alerts
|

A Synaptic Vesicle Protein with a Novel Cytoplasmic Domain and Four Transmembrane Regions

Abstract: Complementary DNA and genomic clones were isolated and sequenced corresponding to rat and human synaptophysin (p38), a major integral membrane protein of synaptic vesicles. The deduced amino acid sequences indicate an evolutionarily highly conserved protein that spans the membrane four times. Both amino and carboxyl termini face the cytoplasm, with the latter containing ten copies of a tyrosine-rich pentapeptide repeat. The structure of synaptophysin suggests that the protein may function as a channel in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
158
0
3

Year Published

1988
1988
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(163 citation statements)
references
References 16 publications
2
158
0
3
Order By: Relevance
“…As far as we are aware, the 'signal' in the synaptophysin molecule that is responsible for its endocytosis has not been identified. In light of what is known about endocytotic signals in other proteins (Davis et al, 1986;Collawn et al, 1990), it is tempting to speculate that some of the tyrosines present in the cytoplasmic tail of synaptophysin (Buckley et al, 1987;Leube et al, 1987;Sudhof et al, 1987) the plasma membrane was a relatively rapid process, the arrival at its final destination, the SLMVs, took significantly longer, leveling off after 3 h of chase. We believe that in the period between its appearance at the plasma membrane and its arrival in SLMVs, synaptophysin cycled for several times between the early endosome and the plasma membrane ( Figure 9, steps 2 and 3 In light of the cycling of synaptophysin between the plasma membrane and early endosomes discussed above, we find it likely that the transport of newly synthesized synaptophysin from the plasma membrane to SLMVs occurred via early endosomes ( Figure 9, step 4), although we do not have direct evidence for this assumption.…”
Section: Resultsmentioning
confidence: 99%
“…As far as we are aware, the 'signal' in the synaptophysin molecule that is responsible for its endocytosis has not been identified. In light of what is known about endocytotic signals in other proteins (Davis et al, 1986;Collawn et al, 1990), it is tempting to speculate that some of the tyrosines present in the cytoplasmic tail of synaptophysin (Buckley et al, 1987;Leube et al, 1987;Sudhof et al, 1987) the plasma membrane was a relatively rapid process, the arrival at its final destination, the SLMVs, took significantly longer, leveling off after 3 h of chase. We believe that in the period between its appearance at the plasma membrane and its arrival in SLMVs, synaptophysin cycled for several times between the early endosome and the plasma membrane ( Figure 9, steps 2 and 3 In light of the cycling of synaptophysin between the plasma membrane and early endosomes discussed above, we find it likely that the transport of newly synthesized synaptophysin from the plasma membrane to SLMVs occurred via early endosomes ( Figure 9, step 4), although we do not have direct evidence for this assumption.…”
Section: Resultsmentioning
confidence: 99%
“…From the amino acid sequence deduced from cDNAs encoding p38/synaptophysin, a model with several membrane spanning polypeptide segments and a carboxy-terminal protein domain exposed to the cytoplasmic surface has been constructed [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested to form a transmembrane channel for ions, or to interact with cytoplasmic factors via its cytoplasmic domain [7]. Since synaptophysin binds Ca 2+, it may also play a role in the release of neurotransmitters stored in clear (synaptic) vesicles [3].…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: depression; psychopharmacology; psychosis; SSRI; synapsin; synaptophysin INTRODUCTION Synaptic vesicle proteins (SVP) such as synapsin I-III, synaptophysin, synaptotagmin, and synaptobrevin (VAMP -vesicle-associated membrane protein) play a critical role in synaptic plasticity, and are required for vesicle fusion and neurotransmitter release. [1][2][3][4][5][6] Hence, changes in the expression of these proteins may contribute to the molecular effects of antidepressant treatment and associated behavioral and cognitive alterations. Previous studies have shown that antidepressants modulate de novo gene transcription and synthesis of proteins involved in neural and synaptic plasticity; in a recent transcriptomic study, a decreased expression of VAMP was found with imipramine and sertraline.…”
mentioning
confidence: 99%